1974
DOI: 10.1128/aem.28.6.987-991.1974
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Plants and Soil as a Reservoir for Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa was detected in 24% of the soil samples but in only 0.13% of the vegetable samples from various agricultural areas of California. The distribution of pyocin types of soil and vegetable isolates was similar to that of clinical strains, and three of the soil isolates were resistant to carbenicillin. Pseudomonas aeruginosa multiplied in lettuce and bean under conditions of high temperature and high relative humidity (27 C and 80-95% relative humidity) but declined when the temperature and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 13 publications
1
81
0
1
Order By: Relevance
“…However, a comprehensive literature screen revealed that the overwhelming majority of intentionally isolated environmental strains are of aquatic origin, with large isolate numbers and high isolation efficiency (Ringen and Drake, 1952;Mutharia et al, 1982;Pellett et al, 1983;Romling et al, 1994;2005;Ahlén et al, 1998;Aoi et al, 2000;Bhattacharya et al, 2000;de Victorica and Galvan, 2001;Kimata et al, 2004;Muscarella, 2004;Pirnay et al, 2005;Khan et al, 2007). In contrast, the few studies on intentional isolations from soil report remarkably low efficiency (Ringen and Drake, 1952;Green et al, 1974;Holden et al, 1996;Aoi et al, 2000). From more than 223 soil samples, only from 24% out of 58 samples (Green et al, 1974), 16% of unknown sample number (Holden et al, 1996;Ferguson et al, 2001), 3% out of 100 samples (Ringen and Drake, 1952), and 0% out of 65 samples (Aoi et al, 2000) a successful isolation was reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, a comprehensive literature screen revealed that the overwhelming majority of intentionally isolated environmental strains are of aquatic origin, with large isolate numbers and high isolation efficiency (Ringen and Drake, 1952;Mutharia et al, 1982;Pellett et al, 1983;Romling et al, 1994;2005;Ahlén et al, 1998;Aoi et al, 2000;Bhattacharya et al, 2000;de Victorica and Galvan, 2001;Kimata et al, 2004;Muscarella, 2004;Pirnay et al, 2005;Khan et al, 2007). In contrast, the few studies on intentional isolations from soil report remarkably low efficiency (Ringen and Drake, 1952;Green et al, 1974;Holden et al, 1996;Aoi et al, 2000). From more than 223 soil samples, only from 24% out of 58 samples (Green et al, 1974), 16% of unknown sample number (Holden et al, 1996;Ferguson et al, 2001), 3% out of 100 samples (Ringen and Drake, 1952), and 0% out of 65 samples (Aoi et al, 2000) a successful isolation was reported.…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa detection sensitivity, 1 ml of suspension was used with the soil samples from Burkina Faso as these soils contained high quantities of sand, low quantities of organic matter, and therefore, yielded clear soil suspensions. In addition, enrichment assays were performed by transferring 2 g of soil into 20 ml of a salt solution supplemented with acetamide, as described previously (Green et al 1974). Inoculated enrichment broths were incubated for 3 days at 28°C with shaking at 180 rev min À1 .…”
Section: Enumeration Of Culturable Pseudomonas Aeruginosamentioning
confidence: 99%
“…It has been frequently isolated from water sources including rivers (Pirnay et al 2005), sea water (Kimata et al 2004), bottled and tap waters (Hunter 1993) and wastewaters (Filali et al 2000). Its isolation from ornamental plants (Cho et al 1975) or vegetables (Wright et al 1976) as well as its detection in hydrocarbon-contaminated environments (Kaszab et al 2010) or agricultural lands (Green et al 1974;Marques et al 1979) have also been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas aeruginosa is an opportunistic human pathogen that occurs naturally in a variety of habitats including soil (Green et al, 1974;Youenou et al, 2014) and, especially, water, both fresh (Pellett et al, 1983;Römling et al, 1994;Aoi et al, 2000;Howard et al, 2004;Pirnay et al, 2005;Khan et al, 2007;Nonaka et al, 2010;Selezska et al, 2012) and marine (Römling et al, 1994;Howard et al, 2004;Kimata et al, 2004;Nonaka et al, 2010), often at sites of pollution (de Vicente et al, 1990;Pirnay et al, 2005) and in wastewater (Ringen and Drake, 1952;Ziegert and Stelzer, 1986;Howard et al, 2004). In these environments, the organism will encounter a variety of stresses, naturally derived [e.g.…”
Section: Introductionmentioning
confidence: 99%